Variasi Kadar Aspal pada Perkerasan Lentur Diperkuat dengan Geosintetik - Nugroho, Soewignjo Agus (MEDIA KOMUNIKASI TEKNIK SIPIL, 2006)
Reflection crack is one type of road crack. Repairing is usually done by overlay. This research examine role of geosintetic as reinforcement in overlay of flexible pavement. This research is done by making a beams model made of aggregate and asphalt, representing flexible pavement. Models are tested with cyclic loads. Observation is focused on the influence of asphalt content to the rate of crack propagation. Results shows that geosintetics reduced rate of crack propagation, while optimum asphalt content still should be used in design. Keywords: geosintetics, overlay, reflection crack, rate of crack propagationPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/3948[How to cite: Nugroho, S.A., 2006, Variasi Kadar Aspal pada Perkerasan Lentur Diperkuat dengan Geosintetik, Jurnal Media Komunikasi Teknik Sipil, Volume 14, Nomor 3, pp. 213-223]